Towards Sustainable Solid Waste Management Systems: Empirical Evidence From Northern Malawi - Tommy Wakana Kamanga; Moses MN Chitete; Bernard CG Kamanga; Chitsanzo Damazio; Yamikani Yafeti; Mary Sibande (SAGE Publishing, 2024)
Solid waste management system in Mzuzu City is a growing concern due to its inefficiency and the resulting effect of accumulation of solid waste. In light of this environmental challenge, a study was conducted to assess the system's effectiveness. Through a mixed methods approach and random sampling, 400 respondents from 5 different areas of the city of Mzuzu were selected to provide comprehensive and unbiased responses. It was found that both the public and private sectors lack a complete commitment to sustainable waste management, citing reasons such as limited knowledge on recycling benefits, inadequate infrastructure and budgetary constraints. As a solution, the study proposes a government-led campaign to change attitudes towards waste production and promote recycling. Additionally, a Public-Private Partnership (PPP) should be utilised to develop policies and strategies that encourage private sector involvement in eco-friendly waste management. To further enhance recycling practices, support is needed in transitioning to circular economy waste management practices through regular education and training.